2020
DOI: 10.3928/01477447-20200619-01
|View full text |Cite
|
Sign up to set email alerts
|

Peri-implant Fractures Following Hook Plate Fixation for Unstable Distal Clavicle Fractures

Abstract: Clavicle hook plate is a common implant for treating distal clavicle fracture. Although high bone union rate and good functional outcome have been reported, so have several complications, such as osteolysis and fracture of the acromion, loss reduction, hook impingement, and rotator cuff tear. Peri-implant fracture over the medial side of the hook plate is a rare complication. Sporadic cases have been reported, and most of them have had no history of trauma. Between June 2015 and August 2018, 7 patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…However, several studies have revealed a lower complication rate and lower stress on the clavicular midshaft when the hook or plate is bent. 14,17,18 In the current study, bending of the hook plate had a greater effect on decreasing the rate of occurrence of midshaft fractures among elderly than young patients. Although the effect was not statistically significant, it seems reasonable that bending of the hook plate should be encouraged during surgery, especially for elderly patients.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…However, several studies have revealed a lower complication rate and lower stress on the clavicular midshaft when the hook or plate is bent. 14,17,18 In the current study, bending of the hook plate had a greater effect on decreasing the rate of occurrence of midshaft fractures among elderly than young patients. Although the effect was not statistically significant, it seems reasonable that bending of the hook plate should be encouraged during surgery, especially for elderly patients.…”
Section: Discussionmentioning
confidence: 44%
“…14 In a clinical study published in 2020, Ni et al. 14 demonstrated that the type of the most medial screw did not significantly influence the incidence of postoperative clavicular midshaft fractures (cortical screw: 8.3% vs. locking screw: 13.3%).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations